Analysis the effect of reflector (flat mirror, convex mirror, and concave mirror) on solar panel - Yahot Siahaan; Hartono Siswono (Institute of Advanced Engineering and Science, 2019)
At the time of the sun a straight line with solar cells may not necessarily produce the maximum output. Various ways continue to be done in order to get the maximum output. The maximum utilization of output from solar cells will accelerate the function of the solar cell. The use of reflectors is an excellent way to maximum output with effective time. The author will analyze solar cells with flat mirror, convex mirror, concave mirror, and without reflector. Each reflector is given varying treatment by calibrating the angle of the reflector to the solar cell by 60o, 90o, and 120o. After testing and data retrieval turns reflector very influential on the output of solar cells. The solar cell output power increases with each different reflector. Maximum output is obtained in a concave mirror with an angle is 90o.